Optimisation of the sequential extraction of fucoidan and sodium alginate from a Southern African brown seaweed, Ecklonia maxima - Park,Yu Chan (Rhodes University, 2026)
Seaweeds have been used in many industries for their biochemical properties, including as bioactive compounds for pharmaceuticals and nutraceuticals. Seaweeds have been shown to contain various valuable bioactive compounds, such as hydrocolloids, polyphenols and carotenoids. These chemical compounds exhibit different bioactivities, including anti-inflammatory, anti-microbial, anti-oxidant, anti-cancer, anti-diabetic and anti-HIV activity. Furthermore, a recent review in 2020 revealed an increase in the number of studies conducted on alginate and other polysaccharides over the past decade due to a growing awareness of their use as sustainable biomaterials. Therefore, there is a growing demand for polysaccharides from algae, such as alginate, and sulphated polysaccharides, such as fucoidan. The brown seaweed Ecklonia maxima, which is endemic to South Africa, is abundant but underexploited for its bioactive compounds. This study was conducted to optimise various parameters to co-extract fucoidan and sodium alginate and to compare the chemical and physical characteristics of the extracts with those of commercially available fucoidan and alginate. During the first stage of this study, the acidic co-extraction of fucoidan and sodium alginate from Ecklonia maxima was optimised. The optimised parameters for the co-extraction procedure were as follow: pH 1.0 for the delipidation step, 80% (v/v) ethanol for fucoidan precipitation, 0.5 M sodium carbonate addition for converting alginate into sodium alginate, and 70% (v/v) ethanol for sodium alginate precipitation. This method successfully co-extracted fucoidan and sodium alginate with yields of 3.67 and 58.7% (w/w dry mass basis), respectively - from a starting material of 7.5 g. The yield of sodium alginate was greater than any yield reported in the literature. The optimised method was scaled up using an increased starting mass of seaweed, up to 200 g, for the large-scale (LS) extraction. The LS extracts were examined for their purity, chemical composition and physical characteristics, such as viscosity, molecular weight, and structural conformation, compared to small-scale (SS) extracts and commercially available fucoidan and alginate standards. The chemical and physical characteristics of the LS and SS extracts were very similar. The extracts contained almost no contaminants, such as phenolics and proteins, when they were evaluated for purity. The chemical compositions of the extracts were similar to those of their commercial counterparts. Both the commercial standards and LS fucoidan were shown to contain large amounts of D-glucose, L-fucose, and sulphate. In contrast, sodium alginates contained large amounts of D-glucuronic acid, D-mannose, and total uronic acid. Carbazole was used to determine total uronic acid in sodium alginates, which were present in high concentrations for all the sodium alginates; this confirmed that the sodium alginate extracts consisted primarily of uronic acid. Various methods were used to determine the physical characteristics of the fucoidan and sodium alginate, such as Fourier transform infrared (FTIR), nuclear magnetic resonance (NMR), circular dichroism (CD) spectroscopy, molecular weight determination, Congo red, and X-ray diffraction (XRD). FTIR indicated that all the required peaks were present, and the extracted fucoidans and sodium alginates displayed the same FTIR profile typical for the commercial fucoidan and sodium alginates standards, confirming the purity and chemical composition of the extracted compounds. CD spectroscopy indicated a mannuronic to guluronic (M/G) ratio of 1.91 for the LS sodium alginate and 0.76 for the commercial sodium alginate. The viscosity average molecular weight of LS sodium alginate was 447 kDa using the Mark-Houwink-Sakurada equation. Both E. maxima sodium alginates and commercial sodium alginate were suspected of assuming a triple-helical conformation in solution and were amorphous in structure, as confirmed by Congo red and XRD analysis, respectively. In conclusion, this study optimised the co-extraction of fucoidan and sodium alginate from brown seaweed and scaled up the extraction process more than 25-fold with a high level of reproducibility. The SS and LS fucoidan and sodium extracts were confirmed to have very similar chemical and physical characteristics to each other, as well as to the commercial fucoidan and sodium alginate standards. The extracted sodium alginate also had a high viscosity, a high molecular weight, and a high M/G ratio. The sequential and combined extraction method for fucoidan and sodium alginate proposed in this study is indeed a feasible and robust approach and can make a significant contribution to the seaweed biorefinery and greater bioeconomy.
Keywords: Uncatalogued